Spitting in the soup: disain intervensi dalam konseling untuk mereduksi perilaku maladaptif pada remaja - Devi Ratnasari (Teraputik: Jurnal Bimbingan dan Konseling)
Against a variety of events that indicate a lot of maladaptive behavior by teenagers, this article aims to provide insight into the use of the "spitting in the soup" technique as one of the designs in Adlerian counseling that seeks to reduce maladaptive adolescents behavior. This technique is an intervention to make the counselee aware of his wrong actions and should be corrected. Counselee behavior is gradually eliminated by removing rewards earned from his behavior. The technique of "spitting in the soup" has four stages: 1) establishing friendly and intimate relationships with counselees, 2) identifying counselee's basic mistakes, 3) asking questions and asking consent to share insights about inappropriate repetitive behavior patterns, 4) the counselor spits on the soup (the counselee problem) and discussing counselee reaction openly about the steps of the counselor.